A discontinuous deformation analysis of the internal shear restraint mechanism in the sliding instability process of compound slopes. (November 2022) - Lu, Bo; Xu, Dongdong; Zhu, Jiebing; Yi, Tianyu
Abstract: Because of the geometric turning characteristics of its basal sliding surface, the compound slope will undergo internal shear deformation during the sliding process. However, few investigations have been conducted into the accurate location and formation process of the internal shear surface, as well as the internal shear restraint mechanism and its influence on slope stability. Therefore, relevant research was carried out based on the Vajont landslide, which is a typical representative of the compound slope. Firstly, the mechanical equilibrium on the internal shear fracture surface is further taken into account in the Rigid Limit Equilibrium Method (RLEM), and the accurate location of the shear surface was obtained by solving the equilibrium equations on the three sliding surfaces simultaneously. Additionally, a sensitivity analysis of the landslide's mechanical characteristics was conducted. Then, using the Discontinuous Deformation Analysis (DDA) method with hydraulic coupling, the entire instability process of the Vajont landslide generated by reservoir impoundment is simulated, as well as the formation process of the shear surface. The results reveal that the locations of the shear surface derived by the two methods agree well. Meanwhile, an objective shear restraint mechanism exists inside the compound slope, which contributes to its overall stability.